Involutions with fixed points in 2-Banach spaces - M. S. Khan; M. D. Khan (International Journal of Mathematics and Mathematical Sciences)
Some results on fixed points of involution maps in 2-Banach spaces have been obtained. These are extensions of those proved earlier by Goebel-Zlotkiewicz, Sharma-Sharma, Assad-Sessa and Iśeki.